Larangan Zina Dan Pergaulan Bebas Ditinjau Dari Hadist Dan Pasal 284 KUHP - Aji Nugraha; Tajul Arifin (Lembaga Pengembangan Kinerja Dosen, 2024)
This research elucidates the relationship between adultery (zina), Article 284 of the Criminal Code (KUHP), Islamic law, and the teachings of Hadith. Adultery, as a sexual act outside of lawful marriage, is deemed a serious transgression against moral and ethical values within society. Article 284 of the KUHP reinforces the prohibition of adultery and provides a legal framework for its enforcement. Conversely, Islamic law and Hadith teachings offer a strong moral and spiritual perspective on adultery, affirming its strict prohibition and serious consequences for perpetrators. This study also discusses practical measures to avoid adultery and the importance of a holistic approach in addressing this issue within society